To determine which expressions are equivalent to \(0.87 - 4.5 - [5.8 + (-7.8)]\), we first simplify the original expression.
-
Start with the expression inside the brackets: \[ 5.8 + (-7.8) = 5.8 - 7.8 = -2.0 \]
-
Substitute back into the original expression: \[ 0.87 - 4.5 - (-2.0) = 0.87 - 4.5 + 2.0 \]
-
Now simplify \(0.87 - 4.5 + 2.0\): \[ 0.87 - 4.5 = -3.63 \] \[ -3.63 + 2.0 = -1.63 \]
Now that we have simplified the original expression to \(-1.63\), we will examine the provided options to find two expressions that also evaluate to \(-1.63\).
Let's evaluate each option:
A) \(0.87 - 4.5 + (-5.8) + 7.8\)
- Simplifying: \[ 0.87 - 4.5 - 5.8 + 7.8 \]
- This simplifies to: \[ 0.87 - 4.5 + 7.8 - 5.8 = 0.87 - 4.5 + 2.0 = -1.63 \quad \text{(equivalent)} \]
B) \(0.87 + 4.5 - 5.8 + 7.8\)
- Simplifying: \[ 0.87 + 4.5 - 5.8 + 7.8 \]
- This simplifies to: \[ 0.87 + 4.5 + 7.8 - 5.8 = 0.87 + 6.5 = 7.37 \quad \text{(not equivalent)} \]
C) \(0.87 - 4.5 - 5.8 + 7.8\)
- Simplifying: \[ 0.87 - 4.5 - 5.8 + 7.8 \]
- This simplifies to: \[ 0.87 - 10.3 + 7.8 = 0.87 - 2.5 = -1.63 \quad \text{(equivalent)} \]
D) \(0.87 + 4.5 + 5.8 - 7.8\)
- Simplifying: \[ 0.87 + 4.5 + 5.8 - 7.8 \]
- This simplifies to: \[ 0.87 + 4.5 + 5.8 - 7.8 = 0.87 + 2.0 = 2.87 \quad \text{(not equivalent)} \]
E) \(0.87 - 4.5 + 5.8 - 7.8\)
- Simplifying: \[ 0.87 - 4.5 + 5.8 - 7.8 \]
- This simplifies to: \[ 0.87 - 4.5 - 2.0 = 0.87 - 6.5 = -5.63 \quad \text{(not equivalent)} \]
The two equivalent expressions are:
- \(0.87 - 4.5 + (-5.8) + 7.8\) (Option A)
- \(0.87 - 4.5 - 5.8 + 7.8\) (Option C)
Thus, the final answers are A and C.